Prognostic Value of Tumor Mutational Burden Related to Immune Infiltration in Cervical Squamous Cell Carcinoma - Wen, Fang; Ruan, Shuai; Huang, Wenjie; Chen, Xiaoxue; Wang, Yulan; Gu, Suping; Liu, Jiatong; Liu, Shenlin; Shu, Peng (Frontiers in Medicine, 2021)
Cervical squamous cell carcinoma (CESC) is one of the most common causes of women cancer deaths in worldwide. At present, immunotherapy using immune checkpoint blockade (ICB) has improved the prognosis of many cancer patients and neoantigens generated by mutations may serve as potential biomarkers for ICB therapy. In this study, we observed the missense mutations were the most frequent in the landscapes of gene mutation of CESC samples. The higher level of tumor mutation burden (TMB)patients had higher overall survival (OS). And, there was significantly correlated between high TMB group and high fractions of most immune cells. Univariate and multivariate Cox regression analysis determined five hub genes (IFNG, SERPINA3, CCL4L2, TNFSF15, and IL1R1) to build a prognostic model. In the prognostic model, the low-risk group had a better OS. Also, mutations of the five hub genes mainly affect the infiltration level of D8+ T cells and DCs. These results indicated the model might be used to differentiate patients who have a different response to immunotherapy, which makes individualized therapy possible. In conclusion, our study is valuable for exploring the role of TMB related to immune infiltration in CESC. Moreover, the prognosis model may help predict the sensitivity of patients to immunotherapy and provide underlying biomarkers for personalized immunotherapy.